Reading Retardation: The Reading Difficulties and it’s Solutions According to Rushdi Ahmed Tuaima - Wildatul Muyasiroh; R. Umi Baroroh; Wildatul Muyasaroh; Mumammad Ziad Al-Fain (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study aims to understand the concept of reading difficulties especially reading retardation, and the solution to fix that problem, according to Rushdi Ahmed Tuaima. The researcher also used a book by Abdul Hamid Sulaiman to compare the data. This type of research is library research. The method used in this research is a descriptive method with a qualitative approach. The data collection technique used is documentation and observation to know the application for treating reading difficulty in the school. Meanwhile, the data analysis technique used in this research is content analysis.  This research reveals that Retardation reading is a student's slowdown individual process in reading. This is measured not by comparing them with others but by their mental abilities. Rushdi Ahmed Tuaima suggested that the teacher should not force the students to achieve standards that other students have achieved. Teachers must motivate students to restore their self-confidence. Apart from this, exercise is also essential to do.  The treatment of reading difficulties was successfully applied in the 9th grade of Ali Maksum Islamic Junior High School, which improved the student's academic and mental aspects. The researcher hopes this research can be a reference for all teachers to implement for learning reading skills.